Motivational priorities for physical education among students majoring in music - Kosheleva , O.; Sydorchuk , T.; Koryaka , E.; Voloshyna , I.; Samoshkin , V. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The problem of formation of motivation for physical education of students majoring in “Musical Art” is of particular importance due to the fact that almost all musical majors are associated with a high risk of developing certain occupational diseases. Regular physical exercises, rational use of appropriate means of physical education can contribute to the solution of this problem, but the situation is complicated by the fact that, according to scientists, most students studying the specialty “Musical Art” have a low level of motivation for physical education. The study of the motivational priorities of students of music majors for physical education will allow to determine ways to improve the process of physical education. The purpose of the study is to investigate the motivational priorities of students of music majors for physical education in order to determine ways to improve the process of physical education. Research materials and methods. Research was conducted at the Dnipro State Academy of Physical Culture and Sports and the Dnipro Academy of Music of the Dnipropetrovsk Regional Council. In the course of the study, methods were used: analysis and generalization of data from scientific and methodical literature, a pedagogical experiment of ascertaining nature, sociological methods (questionnaires). The results of the questionnaire show that the vast majority of students studying the “Musical Art” specialty are well aware of the importance of physical education for strengthening and preserving health. At the same time, there is an underestimation by students of the professional-applied significance of physical culture, the possibilities of using physical education tools to increase professional productivity, and the prevention of occupational diseases. A significant number of students often experience psycho-emotional stress due to participation in music competitions and concerts, which determines the expediency of mastering technologies for the correction of their psychoemotional state. The reasons causing students’ dissatisfaction with physical education classes are the lack of interesting types of motor activity for them, failure to take into account the specifics of professional activity in the content of classes, excessive workload, lack of an individual approach. Conclusions. In order to increase the effectiveness of the physical education process, it is advisable to: select the means of physical education taking into account the requirements of the future profession for the development of physical qualities, use an individual approach when planning the content of classes and determining the amount of physical exertion, include in the program types of motor activity that are popular among students, include to the content of the theoretical training, questions related to the use of physical education tools to correct the physical and psycho-emotional state, prevention of occupational diseases, independent planning of physical exertion.